The bromodomain inhibitor JQ1 triggers growth arrest and apoptosis in testicular germ cell tumours in vitro and in vivo. Issue 7 (27th December 2016) - Jostes, Sina; Nettersheim, Daniel; Fellermeyer, Martin; Schneider, Simon; Hafezi, François; Honecker, Friedemann; Schumacher, Valerie; Geyer, Matthias; Kristiansen, Glen; Schorle, Hubert
Abstract: Type II testicular germ cell cancers (TGCT) are the most frequently diagnosed tumours in young men (20–40 years) and are classified as seminoma or non‐seminoma. TGCTs are commonly treated by orchiectomy and chemo‐ or radiotherapy. However, a subset of metastatic non‐seminomas (embryonal carcinomas) displays only incomplete remission or relapse and requires novel treatment options. Recent studies have shown effective application of the small‐molecule inhibitor JQ1 in tumour therapy, which interferes with the function of 'bromodomain and extraterminal (BET)' proteins. JQ1‐treated TGCT cell lines display up‐regulation of genes indicative for DNA damage and cellular stress response and induce cell cycle arrest. Embryonal carcinoma (EC) cell lines, which presented as JQ1 sensitive, display down‐regulation of pluripotency factors and induction of mesodermal differentiation. In contrast, seminoma‐like TCam‐2 cells tolerated higher JQ1 concentrations and were resistant to differentiation. ECs xenografted in vivo showed a reduction in tumour size, proliferation rate and angiogenesis in response to JQ1. Finally, the combination of JQ1 and the histone deacetylase inhibitor romidepsin allowed for lower doses and less frequent application, compared with monotherapy. Thus, we propose that JQ1 in combination with romidepsin may serve as a novel therapeutic option for (mixed) TGCTs.